Potential Angiotensin Converting Enzyme Inhibitors from Moringa oleifera - Khan, Huma; Jaiswal, Varun; Kulshreshtha, Saurabh; Khan, Azhar (Recent Patents on Biotechnology, 2019)
Background: Hypertension is the chronic medical condition and it affected billions of people worldwide. Natural medicines are the main alternatives to treatment for a majority of people suffering from hypertension. Niazicin-A, Niazimin-A, and Niaziminin-B compounds from Moringa oleifera ethanolic leave extract were reported to have potent antihypertensive activity. Objective: These compounds were targeted with Angiotensin-converting enzyme [ACE] which is one of the main regulatory enzymes of the renin-angiotensin system. Methods: Protein-ligand docking of these compounds with [ACE] [both domain N and C] was conceded out through Autodock vina and visualization was done by chimera. Pharmacokinetics study of these compounds was predicted by ADME-Toxicity Prediction. Results: Niazicin-A, Niazimin-A, and Niaziminin-B showed high binding affinity with ACE and partially blocked the active sites of the enzyme. Niazicin-A, Niazimin-A and Niaziminin-B showed the estimated free binding energy of -7.6kcal/mol kcal/mol, -8.8kcal/mol and -8.0kcal/mol respectively with C-domain of ACE and -7.9kcal/mol, -8.5kcal/mol and -7.7kcal/mol respectively with N-domain of ACE. The compounds showed better binding energy with angiotensinconverting enzyme in comparison to Captopril -5.5kcal/mol and -5.6kcal/mol and Enalapril [standard] -8.4kcal/mol and -7.5kcal/mol with C and N domain, respectively. Conclusion: Computationally, the selected bioactive molecules have shown better binding energy to known standard drugs which have been already known for inhibition of ACE and can further act as a pharmacophore for in vitro and in vivo studies in the development of alternative medicine.
Keywords: Niazimin-A